Strategies of Interaction between Parents and Preschool Children and Features of Ideas about Parenting - Avdulova, T.P.; Krotova, T.V.; Khuzeeva, G.R. (Psihologo-pedagogičeskie issledovaniâ, 2024)
This article reveals the problem of the relationship between the strategies of interaction of parents with preschool children and ideas about parenting in the context of studying the phenomenon of conscious parenting. Conscious and responsible parenting is considered as a transformation of the activity of education in line with higher mental functions modeled by society. Strategies of interaction of parents with a child reflect, to a greater extent, the behavioral component, while various ideas about parenting reflect, to a greater extent, the cognitive and emotional component of conscious and responsible parenting. The results showed that in the structure of strategies of interaction with a child, parents prefer explanatory and coping strategies. That is, in the parental subculture, these types of interaction are considered the most approved and acceptable in raising children. These strategies are directly correlated with such ideas about their parenting as the breadth of the value sphere in the field of raising children, acceptance of their own parenting, a positive attitude to the main institutions of socialization of the child and a high level of awareness of the age characteristics of the child. The variability of individual interaction strategies is determined by the nature of the connection between different interaction strategies. The results of the study allow us to develop technologies for educating and supporting parents. Diagnostic methods can be used as a tool for forming the metacognitive component of parenting, enhancing awareness of various aspects of the child's socialization. В статье рассматривается феномен осознанного и ответственного родительства. Актуальность исследования обусловлена попыткой выявить характер взаимосвязей стратегий взаимодействия родителей и представлений о родительстве. В рамках данного исследования было сделано предположение, что существует связь между особенностями стратегий взаимодействия с ребенком и характером представлений о родительстве. Представлены результаты эмпирического исследования, проведенного среди родителей детей дошкольного возраста (N=2517), в возрасте от 18 до 60 лет. Применялся комплекс методик «Осознанное и ответственное родительство» Т.П. Авдуловой с соавт., опросник Е.О. Смирновой и М.В. Быковой «Структура родительского отношения» (адаптированный вариант). По результатам исследования было обнаружено, что в структуре стратегий взаимодействия с ребенком родители отдают предпочтение объяснительной и совладающей стратегиям. В родительской субкультуре данные типы взаимодействия рассматриваются как наиболее одобряемые и приемлемые в воспитании детей. Данные стратегии связаны прямой корреляцией с такими представлениями о своем родительстве, как: широта ценностной сферы в области воспитания детей, принятие собственного родительства, положительное отношение к основным институтам социализации ребенка и высокий уровень осведомленности о возрастных особенностях ребенка. Вариативность индивидуальных паттернов поведения родителей определяется характером связей различных стратегий взаимодействия. Результаты исследования позволяют разработать технологии просвещения и сопровождения родителей.